Effects of angiotensin II receptor blockers in the coronary arteries of hypertensive rats: Analysis of elemental distribution using LEXRF. (22nd January 2019) - Pickler, Arissa; Mantuano, Andrea; Mota, Carla L.; Tanure, Tayane; Serqueira, Luanna; Ferreira‐Machado, Samara; Lau, Cláudio S.C.; Salata, Camila; de Almeida, Carlos E.; Nascimento, Alessandro; Sena, Gabriela; Fidalgo, Gabriel; et al.
Abstract : Hypertension is one of the major public health problems worldwide. It can cause severely alterations in artery structure and function such as vascular remodeling. Angiotensin II (Ang II) has been linked to vascular dysfunction. It has been shown that blockade of the Ang II type 1 receptor with an Ang II receptor blocker (ARBs) may reverse vascular pathology independently of blood pressure lowering. There is therefore a special interest in establishing whether antihypertensive treatment may correct in part or completely the structural and functional alterations of arteries. Several studies have shown regression of structural remodeling or of functional alterations of small arteries in spontaneously hypertensive rats (SHR) treated with ARBs agents. However, its efficiency was not verified at elemental level in the literature. Knowledge of the elemental distribution in tissues has a great importance in the study of diseases, because chemical imbalance can alter biological functions. Elemental semiquantitative microanalysis in the coronary artery of normotensive, SHRs, and SHRs rats treated with ARBs (losartan and olmesartan) was performed using low energy X‐ray fluorescence maps acquired on TwinMic X‐ray spectromicroscopy station, located at the Elettra synchrotron radiation facility. Morphological changes in coronary samples were also investigated. The results demonstrate that despite the antihypertensive agents used belong to the same class, their capacities to revert chemical and structural changes in the coronary arteries caused by hypertension are different.